Classroom emotional intelligence and its relationship with school performance (European Journal of Education and Psychology, 2018)
Despite the importance of emotions in classrooms, no measurements have been developed to assess group emotional intelligence (EI). The aim of this work was to develop a questionnaire for measuring group EI (G-TMMS) in educational contexts. The psychometric properties of G-TMMS were examined in a sample of 794 participants (47% female; mean age = 16; SD = 1.4), divided into 59 classrooms. The G-TMMS showed a one-factor structure. It also demonstrated to have adequate internal consistency, temporal stability, and convergent validity. Moreover, group EI was associated with higher group school performance. The implications of this new scale in educational contexts are discussed.